2016
DOI: 10.18632/oncotarget.10710
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative and pro-apoptotic effects of GHRH antagonists in prostate cancer

Abstract: Growth hormone-releasing hormone (GHRH) and its receptors have been implicated in the progression of various tumors. In vitro and in vivo studies have demonstrated that GHRH antagonists inhibit the growth of several cancers. GHRH antagonists, JMR-132 and JV-1-38 inhibit the growth of androgen-independent prostate tumors. Here we investigated the involvement of GHRH antagonists in proliferative and apoptotic processes. We used non-tumoral RWPE-1 and tumoral LNCaP and PC3 human prostatic epithelial cells, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The exposure of RWPE‐1 cells to GHRH results in tumorigenic transformation since these cells acquire characteristics in common with human PCa cells including hyperproliferative activity, increased gelatinolytic activity of MMP‐2, decreased cell adhesion and increased cell migration. In this regard, GHRH receptor antagonists have been reported to block the effects of GHRH 15,27,28 . All this together corroborates the important role of GHRH as a mediator in the initiation and progression of PCa.…”
Section: Discussionsupporting
confidence: 70%
“…The exposure of RWPE‐1 cells to GHRH results in tumorigenic transformation since these cells acquire characteristics in common with human PCa cells including hyperproliferative activity, increased gelatinolytic activity of MMP‐2, decreased cell adhesion and increased cell migration. In this regard, GHRH receptor antagonists have been reported to block the effects of GHRH 15,27,28 . All this together corroborates the important role of GHRH as a mediator in the initiation and progression of PCa.…”
Section: Discussionsupporting
confidence: 70%
“…It is generally accepted that the cell viability correlates well with proliferating potential, and that the conventional approach is the MTT test [31]. The MTT test measures cell viability due to the metabolic activity, by a reduction of the water-soluble, yellow tetrazole salt (MTT) into the insoluble dark blue formazan.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that GHRH can activate the mitogen-activated protein kinase signaling pathway in MDA-MB-231 human breast cancer cells [ 9 ]. Munoz-Moreno et al [ 10 ] showed that the GHRH antagonist inhibits the growth of the tumor by inhibiting the protein kinase B (Akt) and extracellular signal-regulated kinases (ERKs) signaling pathway in prostate cancer cells. Their study also showed that the GHRH receptor is expressed in cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%